2022
DOI: 10.3389/fbioe.2022.887463
|View full text |Cite
|
Sign up to set email alerts
|

Role of CD47-SIRPα Checkpoint in Nanomedicine-Based Anti-Cancer Treatment

Abstract: Many cancers have evolved various mechanisms to evade immunological surveillance, such as the inhibitory immune checkpoint of the CD47-SIRPα signaling pathway. By targeting this signaling pathway, researchers have developed diverse nanovehicles with different loaded drugs and modifications in anticancer treatment. In this review, we present a brief overview of CD47-SIRPα interaction and nanomedicine. Then, we delve into recent applications of the CD47-SIRPα interaction as a target for nanomedicine-based antitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 140 publications
(179 reference statements)
0
2
0
Order By: Relevance
“…LNPs have shown tremendous potential and clinical success due to their biocompatibility and biodegradability and have even been previously applied to aid in CD47-SIRPα blockade. 31,35 LNPs not only prevent cargo degradation in transport but can also be preferentially taken up by phagocytic cells like macrophages, thus specifically homing to these cells. 37−40 In previous work, we demonstrated that nanotherapy can improve the transport and specificity of therapeutics, specifically those directed toward macrophages in liver metastasis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…LNPs have shown tremendous potential and clinical success due to their biocompatibility and biodegradability and have even been previously applied to aid in CD47-SIRPα blockade. 31,35 LNPs not only prevent cargo degradation in transport but can also be preferentially taken up by phagocytic cells like macrophages, thus specifically homing to these cells. 37−40 In previous work, we demonstrated that nanotherapy can improve the transport and specificity of therapeutics, specifically those directed toward macrophages in liver metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…CD47-SIRPα signaling has been targeted mainly by anti-CD47 antibodies used in combination with other checkpoint blockades to enhance anticancer function. Incidentally, many cell types in the body aside from just OvCa cells express the self-promoting CD47 protein. Therefore, targeting CD47 as a form of antibody-based immunotherapy has faced the obstacles of both imprecise delivery as well as a high risk of autoimmunity. To address these limitations, we have developed a CD47-SIRPα therapy, which instead aims to reduce SIRPα expression in macrophages and can be delivered more specifically by lipid nanoparticles (LNPs). LNPs have shown tremendous potential and clinical success due to their biocompatibility and biodegradability and have even been previously applied to aid in CD47-SIRPα blockade. , LNPs not only prevent cargo degradation in transport but can also be preferentially taken up by phagocytic cells like macrophages, thus specifically homing to these cells. In previous work, we demonstrated that nanotherapy can improve the transport and specificity of therapeutics, specifically those directed toward macrophages in liver metastasis. Thus, our strategy relies on the natural phagocytic ability of macrophages to facilitate LNP uptake and consequently deliver short interfering RNA (siRNA) to knock down SIRPα expression.…”
Section: Introductionmentioning
confidence: 99%